Successful management of diastolic heart failure in a patient with restrictive cardiomyopathy following an anterior communicating artery aneurysm clipping - Rajasekar Arumugam; Georgene Singh; Krishnaprabhu Raju; Ramamani Mariappan (Journal of Neuroanaesthesiology and Critical Care, 2017)
Perioperative management of neurosurgical patients with an underlying myocardial dysfunction poses a unique challenge to the neuroanaesthesiologist and the neurointensivist. Sudden catecholamine surge during the aneurysmal subarachnoid haemorrhage (SAH) can cause severe cardiac dysfunction such as myocardial ischaemia and cardiomyopathy. SAH in a patient with restrictive cardiomyopathy could be hazardous to the myocardium leading to severe cardiac morbidity. We report the successful management of an acute post-operative diastolic heart failure with a milrinone infusion in a patient with restrictive cardiomyopathy, following anterior communicating artery aneurysm clipping. We have discussed the 'dual beneficial' role of milrinone on the heart and the brain in this clinical setting. In addition, the importance of peri-operative utilisation of transoesophageal echocardiography and transthoracic echocardiography for the successful management of diastolic heart failure is highlighted.